Energy Efficient Operation of Cellular Network Using On/Off Base Stations - Yong-Hoon Choi; Jungerl Lee; Juhoon Back; Suwon Park; Young-uk Chung; Hyukjoon Lee (International Journal of Distributed Sensor Networks, 2015)
To allow rapid growth of the number of base stations, reducing the energy consumption of the stations, as the main energy consumers in cellular networks, has become an important research topic. In this paper, we attempt to find an adaptive cell zooming method to reduce the energy consumption of base stations. The cell zooming mechanism was formulated as an optimization problem with consideration of varying traffic patterns and interference, as well as the service availability of the whole area. Simulations were then conducted to verify the performance of the proposed cell zooming method. The simulations considered varying traffic conditions, both timely and spatially, in traditional 19-cell configuration. The proposed scheme demonstrated reduction of energy consumption of up to 4.72 times for urban environments and 3.78 times for rural environments against traditional static cell operation.